Editors' Choice—Quantification of the Impact of Chemo-Mechanical Degradation on the Performance and Cycling Stability of NCM-Based Cathodes in Solid-State Li-Ion Batteries. Issue 7 (21st July 2021) - Conforto, Gioele; Ruess, Raffael; Schröder, Daniel; Trevisanello, Enrico; Fantin, Roberto; Richter, Felix H.; Janek, Jürgen
Abstract : The use of solid electrolytes in lithium batteries promises to increase their power and energy density, but several challenges still need to be overcome. One critical issue is capacity-fading, commonly ascribed to various degradation reactions in the composite cathode. Chemical, electrochemical as well as chemo-mechanical effects are discussed to be the cause, yet no clear understanding of the mechanism of capacity fading is established. In this work, a model is proposed to interpret the low-frequency impedance of the cathode in terms of lithium diffusion within an ensemble of LiNi1− x−y Co x Mn y O2 (NCM) cathode active material particles with different particle sizes. Additionally, an electrochemical technique is developed to determine the electrochemically active mass in the cathode, based on the estimation of the state-of-charge via open circuit potential-relaxation. Tracking the length of lithium diffusion pathways and active mass over 40 charge-discharge cycles demonstrates that the chemo-mechanical evolution in the composite cathode is the major cause for cell capacity fading. Finally, it is shown that single-crystalline NCM is far more robust against chemo-mechanical degradation compared to polycrystalline NCM and can maintain a high cycling stability.